Integrating Building Information Modelling and Augmented Reality for Construction Projects in Oil and Gas Industry - Wang, Xiangyu; Truijens, M.; Ding, L.; Hou, Lei; Wang, Ying; Lavender, Matt (Queensland University of Technology, 2013)
Construction site is the place where the process of building or assembling infrastructurehappens. As one of the most complicated type of projects, large scale construction projectsinvolve large human multitasking activities across different geographical locations and awide range of disciplines as well as high frequency exchange of information. The mostcommonly recognized way of executing a project includes preparing the constructiondrawings, planning out the contract, allocating the workload, scheduling, and administeringthe progress. This paper introduces many innovative techniques including AugmentedReality (AR), barcode reading and indoor way-finding technologies, and integrates them asalternative means of executing certain activities of construction project. Using a LiquefiedNatural Gas (LNG) scenario, this paper presents: (i) a study of how AR can be effectivelyused to improve the way the information is accessed; (ii) sensing and tracking technologysuch as barcoding as a technological feasibility of locating a specific component of complexLNG plants based on computer-based information; and (iii) indoor way-finding technologyintegrated with AR, with which the construction worker can easily find out where the exactcomponent is located in a warehouse or actual construction site.